2020
DOI: 10.3389/fmed.2020.00496
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Infectivity of Strains Isolated From Dogs Naturally Infected With Leishmania infantum Present a Distinct Pathogenic Profile in Hamsters

Abstract: Visceral leishmaniasis (VL) is a severe disease caused by Leishmania infantum . Dogs are the parasite's main reservoir, favoring its transmission in the urban environment. The analysis of L. infantum from infected dogs contributes to the identification of more virulent parasites, thereby supporting basic and applied studies such as vaccinal and therapeutic strategies. We proposed the in vitro and in vivo characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…infantum experimental challenge, dermatological changes, mainly alopecia, were observed, especially in the Control, SAP, PSmP, PSmG, LA, and LASAP groups. These changes are consistent with those already reported during the course of VL infection in hamsters [ 50 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…infantum experimental challenge, dermatological changes, mainly alopecia, were observed, especially in the Control, SAP, PSmP, PSmG, LA, and LASAP groups. These changes are consistent with those already reported during the course of VL infection in hamsters [ 50 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…The vaccine efficacy was evaluated by qPCR to quantify the parasite burden in the liver and spleen. This quantification makes it possible to evaluate the potential of vaccine candidates to control the L. infantum infection [ 55 ]. The parasitological data revealed that only the LAPSmP and LAPSmG groups were able to reduce the parasite load in both liver and spleen, demonstrating a notable capacity in controlling parasite spread in hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…After the L. infantum experimental challenge, dermatological changes, mainly alopecia, were observed, especially in the Control, SAP, PSmP, PSmG, LA and LASAP groups. These changes are consistent with those already reported during the course of VL infection in hamsters [50,53].…”
Section: Discussionsupporting
confidence: 92%
“…The vaccine efficacy was evaluated by qPCR to quantify the parasite burden in the liver and spleen. This quantification makes it possible to evaluate the potential of vaccine candidates to control the L. infantum infection [53]. The parasitological data revealed that only the LAPSmP and LAPSmG groups were able to reduce the parasite load in both liver and spleen, demonstrating a notable capacity in controlling parasite spread in hamsters.…”
Section: Discussionmentioning
confidence: 99%